This is the tree : a story of the Baobab - Moss, Miriam; Kennaway, Adrienne, 1945- (La Jolla, CA : Kane/Miller, 2005)
A lyrical description of the ancient baobab tree and how it provides shelter and nourishment to wildlife of the African plain.
First published in Great Britain by Frances Lincoln Limited.
3.1
K-3
Keywords: Baobab -- Ecology -- Africa -- Juvenile literature; Savanna ecology -- Africa -- Juvenile literature; Baobab; Trees; Savanna ecology -- Africa; Ecology -- Africa; Zoology -- Africa; Baobab -- Ecology; Trees; Savanna ecology; Ecology -- Africa; Zoology